EVALUASI KESERASIAN KERJA ANTARA ALAT GALI-MUAT EXCAVATOR KOMATSU PC300-8LC DAN ALAT ANGKUT DUMP TRUCK SCANIA P360 DI AREA PNBP VI UNTUK MENUNJANG TERCAPAINYA TARGET PRODUKSI BATUKAPUR BULAN AGUSTUS TAHUN 2022 PT. SEMEN PADANG - Moudy Intan Fandini; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Semen Padang is one of the company cement producers in Indonesia that are members of in the Semen Indonesia Group. For activity mining , PT. Semen Padang did mining limestone and silica in the Bukit Karang Putih area which became the IUP ( Mining Business Permit ) of PT. Semen Padang. The mining activity conducted by open mine ( quarry ). In to do operation production, PT. Semen Padang cooperates with PT. United Tractors Semen Gresik (UTSG). For the PNBP area of the company using 1 unit tool dig load Komatsu PC300-8LC excavator 4 units tool transport Scania P360 dumptrucks. On August, PT. Semen Padang has set a UTSG production target of 9,000 tons/ day . Whereas realization productivity tool load reached only 2,873 tons/ day and tools transport 1,591 tons/ day . This thing caused by time work tools mechanical actual that is not effective because existence obstacles that cause height loss time. As for some Obstacles observed that is happening queue in crusher area VI for 15 minutes , time circulate tool transport actual for 23 minutes whereas the plan is 15 minutes, and it looks lateness operational tool during not enough more 10 minutes. After calculated match factor value among tool load and tools transport obtained MF < 1, then tool load wait with time wait 44.8 seconds , while tool transport work full . Based on problem just now then one method used is Queuing Theory. PT. Semen Padang, has size arrival with limited number and because only served by one excavator unit then service first coming who will served first FCFS (first come first service). After application theory queue got correct MF value of 1.2 and an increase in productivity tool transport to 2,825 tons/day. Production results after repair increase to 31% of the production target. Because after applied queue theory target 9000 tons/ day not yet is reached, then in achievement of production targets writer assume for reduce time circulate tool load be 15 seconds and time circulate tool transport be 15 minutes, and add tool transport becomes 16 units for 2 work shifts at mining PT. Semen Padang. Obtained results productivity tool transport of 9,012 tons/ day . Percentage productivity to 100.14% of the production target.